Анализ взаимодействия криопротекторов с сывороточным альбумином человека с помощью флуоресцентного зонда ФМЕ - Дюбко, Т.С. (Видавничий дім "Академперіодика" НАН України, 2008)
With the help of the multiparametric fluorescent probe 3-hydroxy-4′-(N,N-dimethylamino)flavone (FME), the interaction of cryoprotectants (CP’s) belonging to several classes of chemicals (glycerol, ethylene glycol, 1,2-propane diol, dimethyl sulfoxide, N,N-dimethyl formamide, and N,N-dimethyl acetamide in concentrations from 0.1 up to 7 М) with human serum albumin (HSA) was investigated. It was established that with increase in the CP’s content in medium, the quantum yield of the probe bound to protein decreases, the ratio of intensities and the mutual position of its N* and T* fluorescence bands are changed. The changes of FME fluorescence parameters are interpreted by taking into account the CP’s competitive interaction with two different probe binding sites on the protein molecule. It is marked that the difference in the CP’s influence on spectral properties of the probe bound to HSA is determined by the concentration and the individual chemical structure of CP’s molecules and, first of all, by their hydrophilichydrophobic balance.